Pathological characteristics of patients who develop hepatocellular carcinoma with negative results of both serous hepatitis B surface antigen and hepatitis C virus antibody. Issue 11 (17th September 2013) - Kondo, Reiichiro; Nakashima, Osamu; Sata, Michio; Imazeki, Fumio; Yokosuka, Osamu; Tanikawa, Ken; Kage, Masayoshi; Yano, Hirohisa; The Liver Cancer Study Group of Kyushu
<x xml:space="preserve">Abstract</x> Aim We tried to characterize the pathological features of patients who developed hepatocellular carcinoma (HCC) with the negative results of both serous hepatitis B surface antigen and hepatitis C virus antibody (non‐B, non‐C). Methods In a multicenter study in Kyushu, Japan, we studied the histopathological characteristics of non‐cancerous liver tissues in 129 patients (103 men and 26 women) with non‐B, non‐C HCC. The histological liver damage was evaluated for fibrosis (stage) and inflammation (grade) according to the Ludwig classification of chronic hepatitis. In addition, we examined the hepatitis B virus (HBV) genome in serum samples and liver tissues of 20 patients with non‐B, non‐C HCC. Results Positivity of serum hepatitis B core (HBc) antibody, alcohol abuse, diabetes and non‐alcoholic steatohepatitis were present in 61 (47%), 76 (59%), 57 (44%) and eight (6%) patients, respectively. The degree of fibrosis was mild (stage 1.6 ± 1.2). The stage of patients with neither serum HBc antibody nor alcohol abuse was significantly lower than the stage of patients with HBc antibody and no alcohol abuse (P < 0.05). HBV genome was detected in 15 cancerous tissues (75%) and 16 non‐cancerous liver tissues (80%) in 20 patients with non‐B, non‐C HCC. Only three of the 20 patients were positive for serum HBc antibody. Conclusion Non‐B, non‐C patients appear to develop HCC at a low stage of fibrosis. Occult hepatitis B virus infection is the major risk factor for HCC of non‐B, non‐C patients in Kyushu, Japan.